RISK MANAGEMENT DURING OUTAGE PROJECTS AT POWER PLANTS - Hlophe, Simphiwe; Visser, Jacobus Krige (The South African Journal of Industrial Engineering, 2018)
Outages are needed for the maintenance of most continuously operated plants such as power plants, refineries, and petrochemical plants. Such plants comprise thousands of items of complex equipment and machinery that operate under rigorous operating conditions. Tasks carried out during outage projects include overhauls, inspections, repairs, replacement of equipment, and modification. Like most complex projects, outage projects have a high risk that there will be cost and schedule overruns. A study was done to investigate the management of risks in outage projects at South African power plants. The main objective was to determine whether project risk management is understood and recognised as a success factor for outage projects. A conceptual framework developed from the literature was used to design a survey questionnaire that was emailed to potential respondents who are involved in the management of outage projects. The results of the survey indicated that ineffective or weak outage risk management often results in large cost and schedule overruns. Effective planning and risk management were identified as the most important success factors for outage projects. The study identified training in risk management, an enabling culture, and management support as areas for improvement in outage project risk management.